Analysis of the Community Satisfaction Index Measurement on Housing and Settlement Infrastructure Services in Gorontalo Province - Amir Abas (CV. GovPlan Indonesia, 2026)
Housing and settlement infrastructure plays a crucial role in enhancing community welfare, socio economic conditions, and public health outcomes. This study evaluates the Infrastructure Service Satisfaction Index (IKLI) for housing and settlement services in Gorontalo Province, Indonesia, during 2022–2025 using a mixed methods approach. Data were collected from 150 beneficiaries of the Decent Housing Program (Rumah Layak Huni) and neighborhood road improvement projects in Pauwo Urban Village and Tolongio Rural Village. Quantitative analysis employed descriptive statistics, independent sample t-tests, and multiple linear regression, while qualitative insights were obtained through participatory digital feedback. The results show that the overall IKLI score reached 84.35, categorized as Very Satisfied, with no statistically significant differences between urban and rural areas. High satisfaction was primarily associated with infrastructure availability and quality, reflecting effective program implementation. Meanwhile, relatively lower scores were observed in employment generation and economic contribution, indicating areas requiring further improvement. Qualitative findings emphasize strong community expectations for enhanced basic services, including drainage, clean water access, public lighting, and sustained housing assistance programs. Overall, the study confirms that housing and settlement infrastructure interventions significantly improve living standards and environmental quality, while highlighting the importance of maintenance systems and sustainability frameworks to ensure long term socio economic benefits.